Flipbook Media Based on STAD Model to Improve Social Studies Learning Outcomes of Grade IV Elementary School - Amalia, Lola; Junaedi, Akhmad (Journal for Lesson and Learning Studies, 2024)
This research was conducted based on problems in the field, namely the lack of relevant learning media and still low social studies learning outcomes compared to other learning. The purpose of this study was to analyze the results of media development, feasibility, and effectiveness of Flipbook learning media as a social studies learning media for grade IV material norms & customs in elementary schools. This research uses the type of R&D (Research & Development) research with the ADDIE development method. Data collection techniques in the form of tests & non-tests include observation, interviews, questionnaires, documentation, and tests. The subjects of this study were 1 media expert, 1 material expert, 1 teacher, and 28 fourth grade students. Data collection instruments used questionnaires & test questions. Data analysis techniques used normality test, t-test, and N-Gain test. The results of the media expert assessment obtained a percentage of 92%, and the material expert obtained a percentage of 91.66%, including very feasible. The t-test results show Flipbook effectively improves social studies learning outcomes. N-Gain results showed an increase in social studies learning outcomes. It is concluded that the use of Flipbook media in social studies learning developed by researchers is valid & feasible to use in learning, and effectively helps students learn so that it can improve the learning outcomes of grade IV elementary school students.